2012
DOI: 10.1264/jsme2.me11281
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analyses of Bacterial, Fungal and Nematode Communities in Andosolic Agricultural Soils in Japan

Abstract: We simultaneously examined the bacteria, fungi and nematode communities in Andosols from four agro-geographical sites in Japan using polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) and statistical analyses to test the effects of environmental factors including soil properties on these communities depending on geographical sites. Statistical analyses such as Principal component analysis (PCA) and Redundancy analysis (RDA) revealed that the compositions of the three soil biota commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Arbuscular mycorrhizal fungal community composition in field soils was also shown to be the product of both dispersal and environmental variables [54]. In different studies, a range of physico-chemical parameters was found to structure the mycobiomes of soils sampled along a 2,370 km latitudinal gradient in the southern maritime Antarctic [55], in alpine soils [38], as well as field soils in Texas [56] and Japan [57]. By contrast, Hovatter et al [28] did not find evidence for either species sorting or dispersal limitation to be acting on a regional scale, on fungal community composition in the rhizosphere of Lobelia siphilitica plants or adjacent bulk soil.…”
Section: Soil Mycobiomes Are Spatially Structured Over a Broad Scalementioning
confidence: 99%
“…Arbuscular mycorrhizal fungal community composition in field soils was also shown to be the product of both dispersal and environmental variables [54]. In different studies, a range of physico-chemical parameters was found to structure the mycobiomes of soils sampled along a 2,370 km latitudinal gradient in the southern maritime Antarctic [55], in alpine soils [38], as well as field soils in Texas [56] and Japan [57]. By contrast, Hovatter et al [28] did not find evidence for either species sorting or dispersal limitation to be acting on a regional scale, on fungal community composition in the rhizosphere of Lobelia siphilitica plants or adjacent bulk soil.…”
Section: Soil Mycobiomes Are Spatially Structured Over a Broad Scalementioning
confidence: 99%
“…The composition of soil invertebrates is commonly assessed by first extracting the organisms from the soil using a combination of approaches including pitfall traps (Drummond et al 2015) and modified Tullgren and Baermann funnels (Bao et al 2012), each of which rely on the capture of organisms during active movement. Similarly, aerial insects may be captured using malaise traps (Yu et al 2012).…”
Section: Reducing Sample Volumes For Dna Extractionmentioning
confidence: 99%
“…Also, the presence and absence of specific pathogens were similar in both the vegetable and the environmental samples. Agricultural importance of the current study Indeed, various earlier studies demonstrated the ability of water bodies to disseminate numerous microorganisms into the plantation soils, and to some extent unraveled the ability of organic fertilizers to propagate pathogenic bacteria into the vegetation objects (Munshi et al, 2012;Khan et al, 2014;Khairuzzaman et al, 2014;Ali, 2013;Chigor et al, 2013;Bao et al, 2012;FAO, 2012;Uddin et al, 2012;Faruque et al, 2003). These microorganisms, especially Bacillus spp., E. coli, Staphylococcus aureus, Pseudomonas spp.…”
Section: From Where the Contamination Generated?mentioning
confidence: 72%